Mathematical Disposition of Students Through the Application of the CTL to Basic Statistics Lectures - Delyana, Hafizah; Gistituati, Nurhizrah; Asmar, Ali; Yerizon, Yerizon; Armiati, Armiati; Ramadoni, Ramadoni; Melisa, Melisa (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
Mathematical disposition is one aspect that influences a person's success in learning, because mathematical disposition is a person's attitude towards appreciating mathematics. This research aims to describe the mathematical disposition of students in the Mathematics Education Study Program at PGRI University of West Sumatra in the Basic Statistics course. The research subjects were 28 students from the class of 2021. The instruments used were a mathematics disposition questionnaire and interview sheets. Mathematical disposition is seen using 6 indicators, namely: 1) self-confidence, 2) curiosity, 3) feeling capable, 4) happy, diligent and diligent, 5) flexible, 6) reflective. The data analysis technique uses quantitative descriptive analysis techniques in the form of percentages. The results of this research show that learning outcomes have increased from the average pretest score (62) to posttest score (87). Based on the results of the Shapiro-Wilk statistical test, it was obtained that 0.03 was smaller than 0.05 and had a normal distribution, so the results of this research were acceptable and had a significant effect on students' mathematical disposition through the CTL approach.